Polymer/nanodiamond composites - a comprehensive review from synthesis and fabrication to properties and applications - Karami, Pooria; Salkhi Khasraghi, Samaneh; Hashemi, Mohammadjafar; Rabiei, Sima; Shojaei, Akbar (Advances in colloid and interface science, 2019)
Nanodiamond (ND) is an allotrope of carbon nanomaterials which exhibits many outstanding physical, mechanical, thermal, optical and biocompatibility characteristics. Meanwhile, ND particles possess unique spherical shape containing diamond-like structure at the core with graphitic carbon outer shell which intuitively contains many oxygen-containing functional groups at the outer surface. Such superior properties and unique structural morphology of NDs are essentially attractive to develop polymer composites with multifunctional properties. However, despite a long history from the discovery of NDs, which is dated back to the1960s, this nanoparticle has been less explored in the field of polymer (nano)composites compared with other carbon nanomaterials, e.g. carbon nanotube (CNT) and graphene. However, open literature indicates that research works in the field of polymer/ND (PND) composites have gained great momentum in the past half a decade. The present article provides a comprehensive review on recent achievements in ND based polymer composites. This review covers a very broad aspect from the synthesis, purification and functionalization of NDs to dispersion, preparation and fabrication of polymer/ND (PND) composites with a look in their recent applications for both structural and functional basis. Therefore, the review would be useful to pave the way for researchers to take some advancing steps in this respect. [Display omitted] •An overview on polymer/nanodiamond (PND) composites with a new look at processing-structure-properties relationship.•ND exhibits a unique structure with outstanding inherent properties.•Detailed ND dispersion techniques and PND fabrication protocols are given.•The latest achievements of PND characterizations are reviewed.•The potential aptitude of PNDs in structural and functional applications is demonstrated.